Mixed muco-cutaneous pemphigoid: Clinical and immunological features of 15 cases - Janela, Raphaël; Ishii, Norito; Castel, Marion; Jouen, Fabienne; Cellier, Lucie; Courville, Philippe; Joly, Pascal; Hébert, Vivien (Frontiers in Immunology, 2023)
Introduction We describe a series of patients whose auto-immune bullous skin disease (AIBD) of the dermal-epidermal junction (DEJ) was characterized by clinical, immunological and ultrastructural features intermediate between bullous pemphigoid (BP) and mucous membrane pemphigoid (MMP), and a recalcitrant course. Patients and Methods From the database of the French reference centre for AIBD, we screened all the patients who were referred for an AIBD of the DEJ with a mucosal involvement, who neither met the diagnostic criteria for the diagnosis of BP, nor were typical of MMP. Sera were analysed by NC16A-ELISA and immunobloting against the C-terminal and LAD-1 parts of BP180. Skin biopsies were studied by direct immunoelectron microscopy (IEM). Results Fifteen patients (4 males, 11 females) of mean age 70.8 ± 11.8 years were included. The mucosal involvement was localized in oral cavity in all cases and in pharyngeal/laryngeal or genital area in 8 (53%), and 6 patients (40%), respectively. No patient had ocular involvement, nor atrophic or fibrosing scars. All patients had extensive skin lesions (mean BPDAI score =65.9 ± 24.4), which predominated on the upper body part. Direct IEM performed on 8 patients showed IgG deposits on the lamina lucida in all cases, and the lamina densa in 5 cases. All sera recognized NC16A, while none recognized BP-230 in ELISA. 10 out of the 13 tested sera (76.9%) contained IgG which recognized the C-terminal domain of BP180 and 10 sera (76.9%) the LAD-1 domain of BP180. Patients poorly responded to super potent topical corticosteroids and were treated with oral corticosteroids ± immunosuppressant in 13 cases (86.6%). Conclusion This mixed muco-cutaneous pemphigoid differs from BP by the younger age of patients, multiple mucosae involvement, circulating antibodies against both the C- and N-terminal part of BP180, and very poor response to topical CS. It differs from MMP by extensive inflammatory skin lesions, absence of ocular involvement and atrophic/fibrosing scars.